Controlling knowledge: religion, power, and schooling in a West African Muslim society - Brenner, Louis (Indiana University Press, 2001)
Machine generated contents note: Chapters -- 1. Knowledge and Power in Pre-Colonial Muslim Societies -- Muslim schooling and the esoteric episteme -- Legitimay, knowlkdge andpower -- 2. Medersas, French and Islamic -- The French midersas -- The Origins of the Islamic Midersa Movement -- -Bamako -- -Kayes -- -Segu -- 3. Reform and Counter-Reform: the Politics of Muslim -- Schooling in the 1950s -- The social and political context of reform -- The politics of counter-reform -- 4. Discourses of Knowledge, Power and Identity -- Muslim doctrinal politics: a discourse about ignorance and truth -- The French, the Africans and the Muslims: a discourse about the -- Other -- Identiy as a transformative system -- 5. Power Relations in the Postcolony -- Knowledge andpower in the Republic of MaH -- Islamic resurgence and the materialization of Islam -- 6. The Dynamics of Medersa Schooling -- The expansion of the midersa network -- The socio-economic roots of midersa schooling: changing -- regious subjectivities -- The social constituencies of the midersas -- -Founders, directors and teachers -- v -- -Parents -- -Students and youth -- 7. Islam, the State and the Ideology of Development The -- Politics of Muslim Schooling in the 1980s -- The domestication of the mdersas -- The invisibility of the medersas: discursive patterns in the public arena -- The exclusion of the midersas the 4me Projet Education -- CGoverning men as things' development as a resource of extraversion -- 8. Reprise: Reassessing the Terms of Analysis -- Bibliography -- Index